Perimyocarditis secondary to pegylated interferon alpha 2a in chronic hepatitis C - Myriam, Echeikh; Asma, Kochlef; Hela, Elloumi; Kais, Battikh; BelHassen, Abdennebi; Dalila, Gargouri; Jamel, Kharrat; Abdeljabbar, Ghorbel (International Journal of Hepatology, 2010)
Treatment of chronic hepatitis C is based on combination of pegylated interferon with ribavirin. There are many adverse effects of pegylated interferon which can lead to stop the treatment definitively. Cardiovascular toxicity of pegylated interferon was rarely described in chronic hepatitis C. We report the case of perimyocarditis due to pegylated interferon used with ribavirin during the treatment of chronic hepatitis C International Journal of Hepatology Vol.1(3) 2010 pp.44-45